Story of my life - Lucy Score (UK Hodder and Stoughton, 2025)
big-city romcom author who no longer believes in real-life happily ever afters seeks inspiration by buying a house-and a spot on the town council-in a small lake town that needs its own happily ever after.
Keywords: American English Fiction